Behavioral and psychosocial factors and their effects on insomnia among people undergoing entry quarantine in hotels during COVID-19 pandemic: a cross-sectional study in Guangzhou, China - Rui Luo; Jinghua Li; Menglin Shang; Zhili Peng; Zhiwei Wang; Jing Gu (BMC, 2023)
Abstract Background The COVID-19 pandemic continues to impact global health and China requires a 14-day quarantine for individuals on flights with positive COVID-19 cases. This quarantine can impact mental well-being, including sleep. This study aims to examine the impact of psychosocial and behavioral factors on insomnia among individuals undergoing quarantine in hotels. Methods This study was a cross-sectional survey carried out in Guangzhou, China. The data was gathered through online questionnaires distributed to international passengers who arrived in Guangzhou on flights and were required to undergo a 14-day quarantine in hotels arranged by the local government. The questionnaires were sent to the participants through the government health hotline "12,320." Results Of the 1003 passengers who were quarantined, 6.7% reported significant anxiety and 25.0% had varying degrees of insomnia. Anxiety was positively associated with insomnia (β = 0.92, P < 0.001), while collectivism (β = -0.07, P = 0.036), indoor exercise (β = -0.50, P < 0.001), and the perceived people orientation of the public health service (β = -0.20, P = 0.001) were negatively associated with insomnia. The study also identified moderating effects, such that a higher sense of collectivism, a greater frequency of indoor exercise, and a higher perception of the people-oriented of the public health service were associated with a lower impact of anxiety on insomnia. These moderating effects were also observed in participants with varying degrees of insomnia. Conclusions This study reveals that a proportion of people undergoing entry quarantine experience insomnia and confirms how psychosocial and behavioral factors can alleviate insomnia in this population.